Growth of morel berry (Physalis angulata L.) from different cutting types and plant growth regulators - Hevia Purnama Sari; Ferziana Ferziana; Hilman Hidayat; Riana Jumawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Morel berries are generally propagated using seeds, and vegetative propagation could be an alternative for rapid propagation. This research aimed to evaluate morel berry seedlings from different cutting types and natural plant growth regulators. This research was carried out from May to October 2024 at Plant Laboratory 3, Politeknik Negeri Lampung, Lampung. The experiment was arranged in a randomized complete block design with two factors, i.e., cutting type and plant growth regulators. Observation variables included growth percentage, number of shoots, and shoot length. Data were analysed using analysis of variance (ANOVA) followed by the DMRT test at the 5% level. Based on data, there is no interaction between the first factor (cutting type) and the second factor (PGR). Vegetative propagating of themorel berry using shoot cuttings had a growth percentage of 81%. PGR from mungbean sprout extract had higher growth stimulation than other sources. A more in-depth study is needed regarding the appropriate concentration for each type of PGR. Keywords: ciplukan; natural PGR; shoot cutting; stem cutting; vegetative propoagation